An Analytical Workof Employee’s Inclination towards Use of Core Banking Solution - Ashwini R. Chavan,R. D. Kumbhar (International Journal of Advanced Science and Technology, 2020)
A core banking solution is a boon for the banking sector. In this competitive era of globalization, unlike any other industry banking industry too facing many issues. Although public and private sector banks have already adopted the influence of the IT industry in the banking sector and reaching new heights every day. According to various reports and literature Implementations of CBS increases efficiency by reducing the workload of staff, help to increase accuracy, speed, saves time, money and efforts of employees and customers. Public and private sectorbanks have already adopted CBS but yet cooperative banks are still struggling with the adoption problems of CBS. Employees are the most important part of the bank. And so it is necessary to understand their views, problems, inclination of these stalwarts. In this paper to understand and analyze employee’s inclination towards the use of CBS, the researcher has used a structured questionnaire to collect the data from a convenience sample of 76 bank employees from various cooperative banks in Pune city. A hypothesis has been set and to get the correct results Frequency and Percentage analysis and t-tests areapplied for data analysis and understanding. Also, charts and tables are prepared for a better understanding of the findings.